2019
DOI: 10.1002/hed.25675
|View full text |Cite
|
Sign up to set email alerts
|

Free posterior tibial artery perforator flap for 2‐stage tracheal reconstruction in patients after resection of well‐differentiated thyroid carcinoma invading the trachea

Abstract: Background The present study was conducted to explore the efficacy of using a free posterior tibial artery perforator flap (FPTAPF) for trachea reconstruction after resection of well‐differentiated thyroid carcinoma (WDTC) invading the trachea. Methods We retrospectively collected and analyzed clinical and surgical data from 14 patients who underwent tracheal reconstruction using a FPTAPF after resection of WDTC invading the trachea between August 2014 and July 2017. Results Satisfactory tracheal structure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…In our study, postoperative stenosis was not observed clinically or on tracheoscopy at follow‐up. Comparing the findings of our study with those of other series on patients with TC using different techniques, the SCM periosteal flap seemed superior to free flaps and secondary closure in terms of achieving a stable airway 13‐18 with a low percentage of permanent tracheostomies. Series of ETE anastomoses or sleeve resections showed good results in terms of establishing a stable airway; however, many of the results demonstrated non‐negligible mortality 19‐21 and morbidity 20,22‐24 due to complications (Table 2).…”
Section: Discussionsupporting
confidence: 65%
“…In our study, postoperative stenosis was not observed clinically or on tracheoscopy at follow‐up. Comparing the findings of our study with those of other series on patients with TC using different techniques, the SCM periosteal flap seemed superior to free flaps and secondary closure in terms of achieving a stable airway 13‐18 with a low percentage of permanent tracheostomies. Series of ETE anastomoses or sleeve resections showed good results in terms of establishing a stable airway; however, many of the results demonstrated non‐negligible mortality 19‐21 and morbidity 20,22‐24 due to complications (Table 2).…”
Section: Discussionsupporting
confidence: 65%
“…Compared with that of parotid, temporal, and hypopharynx defects, the reconstruction of tracheal defects is usually completed in a narrow space, so there are higher requirements for the freedom of tissue placement. Therefore, when there are blood vessels in the recipient area, free flaps may be suitable for tracheal reconstruction, which is also related to the length [12,14,15], but they also have some disadvantages. ALT flaps are also ideal for head and neck reconstruction, as they are easy to harvest and provide rich tissue volumes and types.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when there are blood vessels in the recipient area, free aps may be suitable for tracheal reconstruction, which is also related to the length of the pedicle. Free radial forearm aps, anterolateral thigh (ALT) aps and posterior tibial artery perforator aps have been successfully used for the reconstruction of tracheal defects [12,14,15] , but they also have some disadvantages. ALT aps are also ideal for head and neck reconstruction, as they are easy to harvest and provide rich tissue volumes and types.…”
Section: Discussionmentioning
confidence: 99%